Watermelon Juice Supplementation Yields Varying Responses in Serum Lycopene Levels (OR29-08-19). (13th June 2019) - Barnes, Garrett; Crowe-White, Kristi; Ellis, Amy
Abstract: Objectives: Lycopene, a potent antioxidant, is not produced endogenously, but watermelon is a rich food source of lycopene. The objectives of this study were to investigate whether watermelon juice is an effective delivery vehicle for lycopene and assess inter-individual differences of circulating lycopene after watermelon juice consumption. Methods: A placebo-controlled, randomized, double-blind, cross-over trial was conducted with 16 postmenopausal women ages 54–67 years. Participants initiated a low-lycopene diet during a one-week run-in period and adhered to this diet throughout the project. For each intervention arm, participants were randomized to consume either a placebo beverage or two 360 mL servings of pasteurized 100% watermelon juice containing 14.4 mg of lycopene daily for four weeks. Following a two-week washout period, participants received the opposite beverage for an additional four weeks. Before and after both intervention arms, fasting blood samples were collected to measure serum lycopene. Results: Watermelon juice supplementation resulted in an average increase in serum lycopene of 7.30 ± 7.55 µmol/L (p < 0.005) with striking inter-individual differences ranging from 0.08 to 26.03 µmol/L. Interestingly, change score analysis revealed significant differences in lycopene response depending on whether participants received the juice or the placebo beverage first (p = 0.001). Conclusions: While a modest increase in circulating lycopene levels were observed, noteworthy individual differences in lycopene responses reveal the complex nature of lycopene's metabolism and bioavailability in the body. Additional research is imperative to identify the mechanisms underlying these differences in order to fully benefit from lycopene's antioxidant potential. Funding Sources: American Heart Association (#16MCPRP27260233).